Goat Meat Does Not Cause Increased Blood Pressure - Katsunori Sunagawa; Tetsuya Kishi; Ayako Nagai; Yuka Matsumura; Itsuki Nagamine; Shuntoku Uechi (Asian-Australasian Journal of Animal Sciences, 2014)
While there are persistent rumors that the consumption of goat meat dishes increases blood pressure, there is no scientific evidence to support this. Two experiments were conducted to clarify whether or not blood pressure increases in conjunction with the consumption of goat meat dishes. In experiment 1, 24 Dahl/Iwai rats (15 weeks old, body weight 309.3±11.1 g) were evenly separated into 4 groups. The control group (CP) was fed a diet containing 20% chicken and 0.3% salt on a dry matter basis. The goat meat group (GM) was fed a diet containing 20% goat meat and 0.3% salt. The goat meat/salt group (GS) was fed a diet containing 20% goat meant and 3% to 4% salt. The Okinawan mugwort (Artemisia Princeps Pampan)/salt group (GY) was fed a diet containing 20% goat meat, 3% to 4% salt and 5% of freeze-dried mugwort powder. The experiment 1 ran for a period of 14 weeks during which time the blood pressure of the animals was recorded. The GS, and GY groups consumed significantly more water (p<0.01) than the CP and GM groups despite the fact that their diet consumption levels were similar. The body weight of animals in the CP, GM, and GS groups was similar while the animals in the GY group were significantly smaller (p<0.01). The blood pressure in the GM group was virtually the same as the CP group throughout the course of the experiment. In contrast, while the blood pressure of the animals in the GS and GY group from 15 to 19 weeks old was the same as the CP group, their blood pressures were significantly higher (p<0.01) after 20 weeks of age. The GY group tended to have lower blood pressure than the GS group. In experiment 2, in order to clarify whether or not the increase in blood pressure in the GS group and the GY group in experiment 1 was caused by an excessive intake of salt, the effects on blood pressure of a reduction of salt in diet were investigated. When amount of salt in the diet of the GS and GY group was reduced from 4% to 0.3%, the animal’s blood pressure returned to normotensive. These results indicate that, as in the case of chicken consumption, prolonged consumption of goat meat does not cause increased blood pressure, rather the large amount of salt used in the preparation of goat meat dishes is responsible for the increase in blood pressure.